2020
DOI: 10.1097/pcc.0000000000002523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optic Nerve Sheath Diameter and Transcranial Doppler As Noninvasive Tools to Detect Raised Intracranial Pressure in Children

Abstract: Objectives: To compare the diagnostic accuracy of the ultrasonography-guided optic nerve sheath diameter with transcranial Doppler-guided middle cerebral artery flow indices against the gold standard invasive intraparenchymal intracranial pressure values in children. Design: A single-center prospective cohort study. Setting: PICU of a tertiary care teaching hospital in North India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The ONSD values were significantly higher in patients compared to those of controls. This result was already found in a usual way, both in adults ( 8 , 19 , 22 , 23 ) and in children ( 1 , 13 , 24 26 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The ONSD values were significantly higher in patients compared to those of controls. This result was already found in a usual way, both in adults ( 8 , 19 , 22 , 23 ) and in children ( 1 , 13 , 24 26 ).…”
Section: Discussionsupporting
confidence: 77%
“…A recent paediatric meta-analysis has reviewed the diagnostic performances of ONSD and found sensitivities between 39 and 100% and specificities between 22 and 100% ( 9 ). Some studies found a good correlation between ONSD and ICP, such as Kerscher ( 10 ) or Padayachy ( 11 ), whereas others do not find this correlation, such as Biggs ( 12 ) and Sharawat ( 13 ). It is noteworthy that few paediatric studies used invasive measurement of ICP ( 10 , 11 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, multiple recent studies evaluated the diagnostic and prognostic validity of TCD in varied cases, where Cardim et al [27] demonstrated agreement between invasive and noninvasive ICP measurements using TCD and optic nerve sheet diameter ultrasound and suggested the potential role for a non-invasive technique for detection of ICH. Thereafter, Sharawat et al [28] assured the use of TCD as a non-invasive diagnostic modality for increased ICP and using Pearson correlation coefficient found the coefficients for optic nerve sheath diameter, pulsatility index, and resistive index were 0.98, 0.914, and 0.833, respectively. Moreover, Roldán et al [29] conducted a meta-analysis for the most effective techniques for the non-invasive multimodal monitoring for traumatic brain injury and concluded that the near-infrared spectroscopy and TCD are the two most prominent and widely used technologies for non-invasive monitoring in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, limited data suggest the TCD-derived PI may be helpful in the detection of intracranial hypertension early in the course of severe TBI. Conversely, the PI was recently investigated within a heterogenous cohort of 30 children with ICP monitors placed (67% infectious, 10% metabolic, 17% immune-mediated, and 7% other) [ 30 ]. Although children with intracranial hypertension had an elevated PI (0.92 ± 0.41) compared to those measured points without intracranial hypertension (0.69 ± 0.27, p < 0.001), the suggested cut-off for a PI value reflecting ICP ≥ 20 mmHg was 0.51 with 89% sensitivity, 10% specificity, 50% positive predictive value, and 47% negative predictive value.…”
Section: Applications In the Pediatric Intensive Care Unitmentioning
confidence: 99%